2016
DOI: 10.1007/s12034-016-1163-5
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical characterization of zinc-substituted calcium phosphates

Abstract: Biocompatible and bioactive calcium phosphates can make chemical bonds with living bones. Improvement of their biological and physicochemical properties can be achieved by doping with various ions that are presented in natural apatites of bones. These substitutions influence lattice parameters, structure and morphology of apatites. In recent times great attention has been devoted to zinc ions that are the second most abundant trace element present in bones. Zinc embedded into calcium phosphate may enhance the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Previous research showed the possibility of replacing calcium in calcium phosphates with Zn ions. In [ 31 ], the preparation and physical-chemical characterization of Zn-substituted calcium phosphate powders was performed. Authors [ 31 ] demonstrated that up to about 10 at.% (about 15 wt%) of Zn ions do not significantly influence the crystal lattice of HA and brushite, whereas authors [ 32 ] showed that Zn can replace calcium in the β-TCP structure up to about 10 at.% with the preference of the Ca(5) site.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research showed the possibility of replacing calcium in calcium phosphates with Zn ions. In [ 31 ], the preparation and physical-chemical characterization of Zn-substituted calcium phosphate powders was performed. Authors [ 31 ] demonstrated that up to about 10 at.% (about 15 wt%) of Zn ions do not significantly influence the crystal lattice of HA and brushite, whereas authors [ 32 ] showed that Zn can replace calcium in the β-TCP structure up to about 10 at.% with the preference of the Ca(5) site.…”
Section: Introductionmentioning
confidence: 99%
“…9,10,[28][29][30] These results provide appropriate situations and capacities for this kind of biomaterial in terms of clinical practice. Therefore, it is worth to mention that although some valuable works related to e-HA and also Si-HA 9,13,18,20,21,[24][25][26][27][28][29][30][31][32][33][34][35] have been done, no study has accomplished to investigate the effect of adding silicon in the structure of e-HA on physical and mechanical properties besides cellular (osteosarcoma cell line: G-292) and antibacterial behaviours using proper analytical techniques such as X-ray diffraction (XRD), X-ray fluorescence (XRF), scanning electron microscope (SEM)/field-emission scanning electron microscope (FE-SEM), inductively coupled plasma (ICP) and Fourier transform infrared (FTIR). For this purpose, e-HA and Si-e-HA were prepared by chemical precipitation method.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, an excess in the Zn 2+ concentration results in an enhanced saturation of apatite units. More Ca 2+ ions are replaced by Zn 2+ , promoting smooth diffused areas in both phosphate region and amide section [29].…”
Section: Resultsmentioning
confidence: 99%